Literature Review: Mediation Effects of Debt Maturity on Good Corporate Governance in Enhancing Financial Performance - M. Hasmil Adiya; Masyuri Hamidi; Rida Rahim; Fajri Adrianto (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
This study proposes a research model to investigate the mediating effect of debt maturity on the relationship between good corporate governance (GCG) and financial performance. The qualitative approach employed is a systematic literature review (SLR) technique, analyzing 11 articles selected from 142 related ones found on the Google Scholar database within the 2010-2021 research range based on inclusion and exclusion criteria. Debt maturity was found to play a crucial role in shaping the effectiveness of GCG mechanisms in managing financial risks and improving financial performance. The proposed research model has implications for researchers and practitioners, providing a basis for future empirical studies exploring the interplay between GCG, debt maturity, and financial performance. For practitioners, it offers a theoretical framework for developing policies and practices promoting effective GCG and optimal debt maturity structures to enhance financial performance. The findings inform the development of policies and procedures that promote good corporate governance and optimal debt maturity structures, leading to improved financial performance. Additionally, the proposed research model may be applied to other contexts, contributing to a better understanding of the role of debt maturity in the relationship between GCG and financial performance.